2019
DOI: 10.13189/ms.2019.070703
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Queuing Performance Using Queuing Theory Model and Fuzzy Queuing Model at Check-in Counter in Airport

Abstract: A queuing system is a process to measure the efficiency of a model by underlying the concepts of queue models: arrival and service time distributions, queue disciplines and queue behaviour. The main aim of this study is to compare the behaviour of a queuing system at check-in counters using the Queuing Theory Model and Fuzzy Queuing Model. The Queuing Theory Model gives performance measures of a single value while the Fuzzy Queuing Model has a range of values. The Dong, Shah and Wong (DSW) algorithm is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Let us emphasize the difference between the approach and results of this paper and the studies on continuous-time random processes with discrete fuzzy states. For example, fuzzy queueing systems were discussed in [9][10][11][12]; stochastic fuzzy dynamic automatic control systems were considered in [13,14]. At the same time, stationary fuzzy random processes and their covariance functions were not addressed in the publications cited above.…”
Section: Khatskevichmentioning
confidence: 99%
See 2 more Smart Citations
“…Let us emphasize the difference between the approach and results of this paper and the studies on continuous-time random processes with discrete fuzzy states. For example, fuzzy queueing systems were discussed in [9][10][11][12]; stochastic fuzzy dynamic automatic control systems were considered in [13,14]. At the same time, stationary fuzzy random processes and their covariance functions were not addressed in the publications cited above.…”
Section: Khatskevichmentioning
confidence: 99%
“…Therefore, according to (11), the spectral density of the FRP X(t) of the triangular form (ξ 1 (t), ξ 2 (t), ξ 3 (t)) is given by…”
Section: The Spectral Density Of a Stationary Frp The Generalized Wie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different queuing models have been developed to observe the queuing behaviour of a system and optimize the queue length. Hidayah Zaki et al, (2019) observed the performance by measuring the average number of customers in the system (Ls), the average number of customers waiting in the queue (Lq), the average time a customer spends in the system (Ws), and the average time a customer spends waiting in the queue (Wq) of an airline company's queuing system using Fuzzy Queuing Model. This model provides fuzzy numbers in a range that guides the operator to ensure maximum output in a specific period by minimizing the service time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Definition 2.9. The extension of fuzzy arithmetic operations of Ming Ma et al [18] to the set of triangular intuitionistic fuzzy numbers based upon both location indices and functions of fuzziness indices. The location indices number is taken in the regular arithmetic while the functions of fuzziness indices are assumed to follow the lattice rule which is the least upper bound in the lattice I ′ …”
Section: ( ) ( )mentioning
confidence: 99%